Ethnobotanical Study of Mamandur Forest (Kadapa- Nallamali Range) in Eastern Ghats, Andhra Pradesh, India - Rambabu2, N. Savitramma2, S.K.M. Basha1*, P. Umamaheswari2, M. (Journal of Phytology, 2011)
The Mamandur forest located on Chennai – Kadapa High way, consists of high degree of phyto diversity along with some highly valuable endemic and endangered species. The forest is deciduous type but mixed with some ever green elements. It is a source of non-wood forest products (NWFP) like fiber, fuel, wood, gum, resin, vegetable, dyes, oil, honey, medicinal plants, bamboo, etc., Endemic and high economic value Pterocarpus santalinus grows luxuriantly in the area. Hedge of elephants are crossing this forests when they are passing from Kuppam to Nallamali forest areas. The forest is providing food and shelter to wild animals like deer, cats, wild dogs, birds and leopards.